2017
DOI: 10.1007/s00394-017-1589-6
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the dietary inflammatory index and prevalence of radiographic symptomatic osteoarthritis: data from the Osteoarthritis Initiative

Abstract: Higher DII values are associated with higher prevalence of radiographic symptomatic knee osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 35 publications
3
31
4
Order By: Relevance
“…Studies investigating the relationship between DII and OA are rare. Along with the results of this study, in A large cross-sectional study, Veronese et al [ 33 ] showed that higher DII is linearly associated to increased prevalence of radiographic symptomatic KOA. Subjects with the highest DII score had a significantly increased occurrence of radiographic symptomatic KOA by almost 40%.…”
Section: Discussionsupporting
confidence: 80%
“…Studies investigating the relationship between DII and OA are rare. Along with the results of this study, in A large cross-sectional study, Veronese et al [ 33 ] showed that higher DII is linearly associated to increased prevalence of radiographic symptomatic KOA. Subjects with the highest DII score had a significantly increased occurrence of radiographic symptomatic KOA by almost 40%.…”
Section: Discussionsupporting
confidence: 80%
“…By using the DII over the past several years, we have learned a lot about differences in dietary consumption, as they relate to inflammation, across a wide variety of populations (50)(51)(52)(53)(54)(55)(56)(57)(58)(59). These studies have involved individuals of both sexes (54 (50,(92)(93)(94)(95)(96)(97). Of course, the primary means through which we have learned about interpopulation differences derives from computing DII [or energy-adjusted DII (E-DII)] scores, conducting statistical analyses using these scores as covariates in analyses, and interpreting results.…”
Section: Additional Insights Based On Collaborative Workmentioning
confidence: 99%
“…The fully adjusted model included also the following covariates: race (whites vs. others); body mass index (as continuous); education (degree vs. others); smoking habits (current and previous vs. others); yearly income (categorized as ≥ or < 50,000$ or missing data); Physical Activity Scale for Elderly score (as continuous); Charlson co-morbidity index; CES-D: Center for Epidemiologic Studies Depression Scale; total energy intake (as continuous); number of frailty indexes at baseline (one vs. none); medical insurance (yes vs. no); transitions in health care during follow-up period. Symptomatic knee OA (Veronese et al, 2017b) (i.e., the presence of painful knee and alterations suggestive for knee OA) was initially considered as covariate, but excluded since the prevalence was not difference across groups and was not associated with frailty at follow-up ( p -value = 0.38 at the univariate analysis).…”
Section: Methodsmentioning
confidence: 99%